219k views
3 votes
5(6t-3)=5t+35

find the value of t​

1 Answer

1 vote

Answer:

t = 2

Explanation:

5(6t-3)=5t+35

Step 1 distribute the 5 by multiplying 5 to what is inside of the parenthesis

5(6t) - 5(3) = 5t + 35

Outcome: 30t - 15 = 5t + 35

Step 2 add 15 to both sides

30t - 15 + 15 = 5t + 35 + 15

Outcome: 30t = 5t + 50

Step 3 subtract 5t from both sides

30t - 5t = 5t - 5t + 50

Outcome: 25t = 50

Step 4 divide both sides by 25

25t/25 = 50 we're left with t = 2

User Manas Bajaj
by
5.0k points